An optimal BMI range associated with a lower risk of mortality among HIV-infected adults initiating antiretroviral therapy in Guangxi, China - Junjun Jiang (Nature Portfolio, 2019)
Abstract Previous studies investigating HIV-infected patients suggested a direct link between underweight and the mortality rate of AIDS. However, there was a lack of evidence showing the optimal range of initial body mass index (BMI) patients maintain during antiretroviral therapy (ART). We aimed to evaluate associations of the BMI values pre-ART and during the entire ART duration with mortality among HIV-positive individuals. In total, 5101 HIV/AIDS patients, including 1439 (28.2%) underweight, 3047 (59.7%) normal-weight, 548 (10.7%) overweight and 67 (1.3%) obese patients, were included in this cohort. The cumulative mortality of underweight, normal-weight, and overweight were 2.4/100 person-years (95% CI 1.9–2.9), 1.1/100 person-years (95% CI 0.9–1.3), and 0.5/100 person-years (95% CI 0.1–0.9), respectively. Cumulative mortality was lower in both the normal-weight and overweight populations than in the underweight population, with an adjusted hazard ratio (AHR) of 0.5 (95% CI 0.4–0.7, p < 0.001) and 0.3 (95% CI 0.1–0.6, p = 0.002), respectively. Additionally, in the 1176 patients with available viral load data, there was significant difference between the underweight and normal-weight groups after adjustment for all factors, including viral load (p = 0.031). This result suggests that HIV-infected patients in Guangxi maintaining a BMI of 19–28 kg/m2, especially 24–28 kg/m2, have a reduced risk of death.